Evaluating Post-Treatment Quality of Life in Cervical Cancer Patients in Tripura, India - Sarada Sutradhar; Satish Kumar Gupta; Partha Sarathi Sutradhar (National Journal of Community Medicine)
Background: In India, cervical cancer (CC) is the most common gynecological cancer. This harms the patient's physical and psychological health, lowering their quality of life (QOL). The study aimed to compare QOL of healthy women and cervical cancer survivors in Tripura, India.